KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT DALAM MERENEGOSIASI NORTH AMERICAN FREE TRADE AGREEMENT (NAFTA) MENJADI UNITED STATES-MEXICO-CANADA AGREEMENT (USMCA) PADA MASA KEPEMERINTAHAN DONALD TRUMP - Balqis Febryani; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzes America known to many countries in the world as the country with the largest economy in the world. In order to maintain its hegemony, the United States has always participated in an international cooperation. But in 2016, the direction of the foreign policy of the United States underwent a significant change. The rise of Donald Trump as the 45th president of the United States, made the foreign policy direction of the United States turn into a nationalist populist direction. With the goal of "Make America Great Again" where Donald Trump wanted to restore the glory of the United States back, Trump changed the foreign policy of the United States to a nationalist "America First". The United States issued a controversial foreign policy of initiating the renegotiation of the NAFTA deal. The renegotiation resulted in a new agreement called USMCA, which has been signed by the three member states of NAFTA. The USMCA trade deal came into effect in 2020. This research uses qualitative methods, with data collection techniques through literature studies sourced from several books, journals, articles, and websites. This research uses the perspective of Neorealism, Foreign Policy theory and the level of analysis of the Nation-State. Foreign policy spending that took the initiative to renegotiate the NAFTA deal into USMCA not only has an impact on the United States, but for countries directly or indirectly having cooperation influence in the North American region can be affected. Keywords: NAFTA, USMCA, Foreign Policy of United States.